Comorbidity of Neurally Mediated Syncope and Allergic Disease in Children - Wang, Yaru; Du, Junbao; Jin, Hongfang; Liao, Ying (Frontiers in Immunology, 2020)
Neurally mediated syncope (NMS) is the most common underlying disease of pediatric syncope, which generally includes vasovagal syncope (VVS), postural tachycardia syndrome (POTS), and situational syncope. Allergic diseases involving the respiratory system, digestive system, skin, and other systems are prevalent in children. In recent years, increasing attention has been paid to children with the comorbidity of NMS and allergic diseases. This article reviewed the featured clinical manifestations and pathogenesis of the comorbidity according to the progress of related studies. Clinical studies have shown that the comorbidity rate of pediatric VVS and/or POTS with allergic diseases amounts to approximately 30-40%, referring to the whole population of children with VVS and/or POTS. Additionally, children with the comorbidity present some relatively special clinical characteristics. A series of mechanisms or regulatory factors relating to allergies, such as the imbalance of vasoactive elements, dysfunction of the autonomic nervous system (ANS) and autoimmunity, may play a role in the development of the comorbidity. Moreover, 90% of children with cough syncope, a type of situational syncope, have a history of asthma, indicating a potential relationship between asthma and NMS. Further studies exploring the clinical characteristics and pathogenesis of the comorbidity are still needed to aid in the diagnosis and treatment of children with NMS.